2020
DOI: 10.1103/physrevd.101.055028
|View full text |Cite
|
Sign up to set email alerts
|

Singlet-doublet fermionic dark matter and gravitational waves in a two-Higgs-doublet extension of the Standard Model

Abstract: We present a study of singlet-doublet vector-like leptonic dark matter (DM) in the framework of two Higgs doublet model (2HDM), where the dark sector is comprised of one doublet and one singlet vectorlike fermions (VLFs). The DM, that arises as an admixture of the neutral components of the VLFs, is stabilized by an imposed discrete symmetry Z 2 . We test the viability of the DM candidate in the light of observations from PLANCK and recent limits on spin-independent direct detection experiments, and search for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 163 publications
(280 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, the observational perspectives on gravitational-waves signals extraction have been tested for some particle physics models [184][185][186] with LISA 120401-7 sensitivity curves. Recently, the model selections and comparisons have been confronted with the real data from the NANOGrav 12.5-year data [187][188][189][190][191][192][193] and LIGO [194,195]. To better extract BSM physics from the phase transition models, more theoretical understandings are needed for the possible features of anisotropies [196] and the non-Gaussianity [197] beyond the simple power-law shapes of the energy density spectrum.…”
Section: (4) Particle Physics Phenomenology On the Phase Transition Modelsmentioning
confidence: 99%
“…On the other hand, the observational perspectives on gravitational-waves signals extraction have been tested for some particle physics models [184][185][186] with LISA 120401-7 sensitivity curves. Recently, the model selections and comparisons have been confronted with the real data from the NANOGrav 12.5-year data [187][188][189][190][191][192][193] and LIGO [194,195]. To better extract BSM physics from the phase transition models, more theoretical understandings are needed for the possible features of anisotropies [196] and the non-Gaussianity [197] beyond the simple power-law shapes of the energy density spectrum.…”
Section: (4) Particle Physics Phenomenology On the Phase Transition Modelsmentioning
confidence: 99%
“…Although the first-order electroweak (EW) phase transition (PT) would have been possible in the framework of SM of particle physics through the Higgs mechanism but with the observed Higgs mass of 125.09 GeV [34][35][36][37] the transition is a smooth cross-over and not a first-order one. However, in literature there are ample references where the authors have shown that SFOPT can be realised by simple extension of SM [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. In the present work however, we primarily explore GW emission from the annihilation of domain walls by proposing a simple extension of SM with two complex scalars.…”
Section: Jhep05(2021)223mentioning
confidence: 99%
“…In refs. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] the authors have proposed different particle physics models for the production of GWs from first-order phase transition but variance from their approaches in this work, we consider an extension of SM with two complex scalars in such a way that it can provide GW production from SFOPT as well as the GW production from unstable domain walls. We constrain the model parameters by using some theoretical and experimental constraints such as vacuum stability, perturbativity and the collider bounds.…”
Section: Jhep05(2021)223mentioning
confidence: 99%
“…Study of such scalar singlet DM has been extended in different directions where additional portal couplings of the scalar are engaged on top of the usual Higgs portal interaction. One such possibility is to include DM portal couplings with new vectorlike leptons [26][27][28][29][30][31][32] and quarks [33][34][35][36][37]. The interesting feature that came out of these studies is the presence of radiative corrections that not only affects the DM annihilations significantly but also leads to interesting observations for DM indirect searches.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution affecting the relic abundance (to some extent) gets decoupled from the ones giving rise to tree level spin independent DM-nucleon scattering and hence DM with mass below 1 TeV is expected to be revived. Although phenomenological implications of such a setup have already been addressed elsewhere from different perspectives [26][27][28][29][30][31][32][33][34][35][36][37], here we have one more motivation and that is to ensure the stability of electroweak vacuum all the way up to the Planck scale. The idea emerges from a recent observation [39] that, though we know fermions coupling to the Higgs contribute negatively to the RG running of quartic coupling λ H in general, the presence of VLQs can actually affect the SUð3Þ gauge coupling in such a way which in turn is useful in keeping λ H positive at all scales.…”
Section: Introductionmentioning
confidence: 99%